Penyuluhan Perbaikan Sistem Ronda Malam Keliling di RT 07 Desa Kedungharjo, Ngawi, Jawa Timur - Novia Faqihatun Nikmah (UIN Raden Mas Said Surakarta, 2021)
This research aims to restore the night patrol system was stopped RT 07 Kedungharjo village. In this research several attempts or the stages in the research are also described in detail. Efforts such as: request for permission to the head of the household, counseling on the importance of night patrols to residents, making a schedule for the night patrol and cleaning the guard post as the final form of the stage this. The method used in this research is a stage consisting of 3 stages. Namely the initial stage of preparation for the implementation stage and the final stage of the evaluation of the activities that has been running. The results of this activity show that the activities have been running for one week does not always go smoothly. There are several obstacles such as some residents who could not attend due to personal matters and factors work So that this is the discussion in the evaluation activities led by the head of the household.